2015
DOI: 10.1534/genetics.115.181149
|View full text |Cite
|
Sign up to set email alerts
|

Stimulation of Chromosomal Rearrangements by Ribonucleotides

Abstract: We show by whole genome sequence analysis that loss of RNase H2 activity increases loss of heterozygosity (LOH) in Saccharomyces cerevisiae diploid strains harboring the pol2-M644G allele encoding a mutant version of DNA polymerase e that increases ribonucleotide incorporation. This led us to analyze the effects of loss of RNase H2 on LOH and on nonallelic homologous recombination (NAHR) in mutant diploid strains with deletions of genes encoding RNase H2 subunits (rnh201D, rnh202D, and rnh203D), topoisomerase … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
63
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(68 citation statements)
references
References 38 publications
4
63
0
Order By: Relevance
“…Although our work and that of O'Connell and colleagues (4) concluded that this protection results from RNase H2's removing R-loops, a different study of RNase H2's activities by Conover and colleagues (5) suggested that this protection is afforded by RNase H2's ability to remove misincorporated nucleotides. In fact, many studies have shown that misincorporated ribonucleotides can lead to DNA damage and mutation in a topoisomerase I-dependent manner (13)(14)(15)(16).…”
Section: Discussionmentioning
confidence: 49%
See 1 more Smart Citation
“…Although our work and that of O'Connell and colleagues (4) concluded that this protection results from RNase H2's removing R-loops, a different study of RNase H2's activities by Conover and colleagues (5) suggested that this protection is afforded by RNase H2's ability to remove misincorporated nucleotides. In fact, many studies have shown that misincorporated ribonucleotides can lead to DNA damage and mutation in a topoisomerase I-dependent manner (13)(14)(15)(16).…”
Section: Discussionmentioning
confidence: 49%
“…Studies of the inactivation of RNase H1 in yeast have shown little effect on chromosome instability (3,4), whereas inactivation of RNase H2 has been shown to increase chromosome instability (4,5). However, results from the Conover study (5) suggested that the elevated instability in the RNase H2-deficient cells is caused by elevated misincorporation of ribonucleotides rather than by the failure to remove hybrids. In contrast, results from the O'Connell study (4) suggested the opposite: that the elevated instability is caused by hybrids rather than by misincorporated ribonucleotides.…”
mentioning
confidence: 99%
“…Although we did observe a small reduction in LOH in the rnh201D pol2-M644L strain relative to the rnh201D strain in one of our LOH assays, the reduction was only 20%. In a similar assay, the rate of LOH in an rnh201D strain was reduced less than twofold by the pol2-M644L mutation (Conover et al 2015).…”
Section: Discussionmentioning
confidence: 93%
“…Although we did observe a small reduction in LOH in the rnh201D pol2-M644L strain relative to the rnh201D strain in one of our LOH assays, the reduction was only 20%. In a similar assay, the rate of LOH in an rnh201D strain was reduced less than twofold by the pol2-M644L mutation (Conover et al 2015).Based on subtle effect of the pol2-M644L mutation, we suggest that most of the LOH in the rnh201D mutant reflects persistent R-loops rather than persistent rNMPs. Our data indicate that RNase H2 can remove most, if not all, of the R-loops that accumulate in the absence of RNase H1, but that RNase H1 can remove only a relatively small fraction of the Figure 6 Classes of red/white sectors resulting from RCO.…”
mentioning
confidence: 76%
“…Somewhat surprisingly, RNA/DNA hybrids were found at higher than normal levels in cell lines from AGS patients with mutations in RNASEH2A , RNASEH2B , SAMHD1 and TREX1 , suggesting hybrids as possible causes of AGS[83]. The debate between consequences of rNMPs in DNA and failure to resolve RNA/DNA hybrids continues.. Two recent studies in S. cerevisiae examining recombination in diploid strains reported genome instability in the absence of RNase H2 but reached opposite conclusions as to the contributions of the two RNase H2 activities to the observed instability [59, 84]. Clearly more work lies ahead that will be aided by a RNase H2-RED (Ribonucleotide Excision Defective) mutant that lacks RER but can hydrolyze RNA/DNA hybrids[85].…”
Section: Ribonucleotides In Dna Of Aicardi Goutières Syndrome (Ags) Amentioning
confidence: 99%